Improved the two DC capacitors’ voltage balancing of three-level NPC inverters applied in electric vehicles - Le Minh Thien, Huynh; Hong Nhu, Nguyen (Tạp chí Khoa học Công nghệ Giao Thông Vận Tải, 2023)
Excessive unbalance of the DC capacitor voltages of the inverter can cause overvoltages on power components and capacitors, causing unintended low-order harmonics on the load side such as second harmonics, 3rd, 4th, 5th, ..., causing direct harm to the motor load, reducing the controllability of the reverse voltage and filter compensating current for the active filter circuit, affect to the performance of electric vehicles (EVs). Therefore, maintaining the DC capacitors' voltage balance will control the multi-level inverter's input quality and ensure the output quality in terms of Total Harmonic Distortion (THD). The paper proposes a method to control the two DC capacitors’ voltage balance of the 3-level inverter, using the principle of offset function separation. The analysis results suggest that the NPC three-level modulation technique should be implemented to satisfactorily achieve the neutral line current (iNP). Compared with recent international publications, the proposed new algorithm can save and reduce switching loss; the transient dynamic response can be adjusted easily. Maintaining the capacitor voltage balance allows the design with the smallest capacity to reduce voltage stress on components. The proposed results are partially verified through simulation and experiment.